Perceptions of studemt nurses of their personal and academic development during placement in the community as a clinical learning environment - N. Dana; N.S. Gwele (AOSIS, 1998)
A descriptive survey was conducted to investigate the perceptions of student nurses about the community as a clinical learning environment. Thirty nine students (21 second years and 18 third years) participated in the study. A seven-point Likert scale questionnaire was used to obtain data on how nursing students perceived the community as a clinical learning environment in facilitating their personal and academic development. The questionnaire items were categorised according to (a) independence on learning, (b) opportunities for learning, peer support, (d) organisational support, (e) quality of supervision, (f) role clarity, and (g) satisfaction with chosen career. Data were analysed using descriptive and inferential statistics. Of the eight clinical learning variables studied, means scores and standard deviations of seven variables yielded positive perceptions of students about the community as a clinical learning environment. On Spearman rank correlation all the variables correlated positively with personal and academic development. A difference on three variables, personal and academic development, opportunities for learning and satisfaction with chosen career was found between perceptions of second and third year students on analysis of variance (ANOVA). In two variables, that is, personal and academic development and satisfaction with nursing as a chosen career, the second year students were more positive than third year students. Third year students perceived the community negatively with regard to opportunities for learning.